Correlational study of vocabulary mastery and cognitive learning style in vocational school - Ujang Suparman (UPT Bahasa Universitas Tanjungpura, 2022)
The research is intended to analyze whether there is a correlation between students’ vocabulary mastery and cognitive learning style with their reading comprehension ability. Methodology: It was conducted in Muhammadiyah Vocational school Bandar Lampung. The sample comprises 30 students using random sampling technique. A questionnaire was used to trace students’ cognitive learning strategy, and two sets of tests were used to measure students’ vocabulary mastery and another to measure their reading ability. The instruments were tried out to determine the quality of validity, reliability, level of difficulty and discriminating power. The findings: It has been found that, first, there is a correlation between vocabulary mastery (X1) and reading comprehension (Y), where rx1.y = 0.35; second, there is a correlation between students’ cognitive learning style (X2) and their reading ability (Y). where rx2.y = 0.95, it is very strong correlation: and finally, there is a composite correlation between X1, X2, and their reading ability (Y). Multiple regression is 0.997 meaning that there is a positive and significant correlation between X1, X2, and Y. It suggests that to improve reading ability, teachers should develop students’ vocabulary mastery and cognitive learning style. Cognitive learning style and vocabulary mastery cannot be separated.